Optimization of power system problems : methods, algorithms and MATLAB codes - Pesaran Hajiabbas, Mahmoud; Mohammadi-Ivatloo, Behnam (Cham : Springer Nature Switzerland AG, 2020)
This book presents integrated optimization methods and algorithms for power system problems along with their codes in MATLAB. Providing a reliable and secure power and energy system is one of the main challenges of the new era. Due to the nonlinear multi-objective nature of these problems, the traditional methods are not suitable approaches for solving large-scale power system operation dilemmas. The integration of optimization algorithms into power systems has been discussed in several textbooks, but this is the first to include the integration methods and the developed codes. As such, it is a useful resource for undergraduate and graduate students, researchers and engineers trying to solve power and energy optimization problems using modern technical and intelligent systems based on theory and application case studies. It is expected that readers have a basic mathematical background.
Includes bibliographical references.
Keywords: MATLAB; Electric power systems; Mathematical optimization; Electronic books